Status of dust pollution and respiratory disease among inhabitants near road construction area in Chabahil - Sankhu road, Kathmandu. - Tandukar,Devika (2017)
SUMMARY: Fine particles in the air is linked with a wide range of acute and chronic illness, such as liung cancer, COPD. Reports show Kathmandu's air has high quantity of pollution because of which massive effects in health can be observed in residents of Kathmandu . Topography of Kathmandu valley is bowl shaped because of this there is restriction in wind movement. Air pollution associated with road construction and increasing number of vehicles which run over the unpaved roads that contributes in re-suspensions of dust in air turned the Valley into a dust bowl which has potential for severe impacts on human health. Worldwide, 5.4% of all deaths can be accounted to ambient air pollution that is about 3.7 million deaths per year. In the context of Nepal , nearly, 36 people out of every 100,000die due to various diseases linked to air pollution(WHO). In 2016, EPI put Nepal at 139th rank among 180 countries in terms of air quality . Improperly planned road expansion , unrestricted vehicle emission and pipe laying work for the Melamchi Water Supply project across Kathmandu Valley can be recognized for the declining position which have posed a serious respiratory health hazard for Valley residents. In 2016, in-charge of respiratory disease unit at TU Teaching Hospital and Norvic International Hospitals said the number of patients suffering from respiratory problems had risen by over 25percent in recent weeks. The general objective of this study is to access the status of dust pollution and respiratory disease among inhabitants near road construction area in Katmandu. Ecological analytical study is conducted and for perception and data triangulation is done through collection of primary data. For cases of respiratory disease, inpatient record from Helping Hands Community Hospitals is chosen and for status of dust pollution, different records and reports are reviewed . For collection of primary data households alongside the under-construction road section of Chabahil-Jorpati is chosen. The sample size for primary data is calculated using sample size calculator, Rasoft which is 170(p+22%,CI+95%,d+0.05) and systematic sampling technique is applied .For collection of secondary data through hospital and AQMS, data collection sheet as data collection tool and record review as technique is used and for collection of primary data on households semi-structured questionnaire as data tool and interview as technique used . For data management and analysis MS-Excel and SPSS is used . Calculations are done using descriptive and inferential statistics as per demand for the study. From this study it is found that daily average levels of PM10 and total suspended particulates in Kathmandu crosses the national standards by more than 20 times. It is also found that though construction acts as the major source for total suspended particulars and PM10 resuspension in the air of Kathmandu as it contributes for 64% for TSP and 53% for PM10 resuspension to other places inside Kathmandu Valley. From the hospital records, it is found that respiratory diseases ( focusing on COPD) has scaled up in last 7 years and the average age of COPD hospitalization has been decreasing trend(i.e. from 65.2 in 2067 to 60.9 in 2073 ). More females are hospitalized for COPD than males. As for trend of pneumonia hospitalization is in year 2071. It is found primary data that 92.9% of the residents in Chabahil- Jorpati area categorize air quality of Kathmandu as poor and view Kathmandu as the most polluted city of Nepal. Majority of the respondents (64.7%) think that the air quality has become much worse in comparison to last year and they report that dust is mainly the common visible sign of air pollution. Most of the respondents (92.4%) think that 12PM -4PM is most polluted time of the day. Among 170 respondents ,87.6% have reported to experience some kind of health effect due to dust pollution. Among those who have experienced health effect, majority of the people have reported increased cough (74.1%) and breathing difficulty (59.2) which exlplains the increased number of hospitalization for respiratory diseases. This study shows that the use of normal (surgical/cloth) type of mask is equivalent to not using mask at all. It shows only the pollution recommended mask ( those with air filters ) are seen to be effective in controlling hazards of air pollution to some level in Chabahil-Jorpati s area but only 5.9% of the respondents have reported to use pollution recommended masks. It is also evident from theX2 test that time of residence is associated with increased health effects in Kathmandu as residents who have lived in Kathmandu for more than 1 year, 93.3% reported to have experienced some kind of health effects in contrast to those residents who have lived in Kathmandu for less than one year (47.6%)reported to have experienced health effects.